Bell polynomials and generalized Laplace transforms. Issue 12 (2nd December 2022) - Ricci, Paolo Emilio
ABSTRACT: An extension of the Laplace transform obtained by using the Laguerre-type exponentials is first shown. Furthermore, the solution of the Blissard problem by means of the Bell polynomials gives the possibility to associate to any numerical sequence a Laplace-type transform depending on that sequence. Computational techniques for the corresponding transform of analytic functions, involving Bell polynomials, are derived.